Cyber Crime Triangle Approach to Encounter Cybercrime - Sri Sundari; Muhammad Haikal Kautsar (Budapest International Research and Critics University, 2021)
This study anlyze and discuss problem in encounter of cyber crime using crime triangle approach. crime triangle approach is necessary in order to understanding cyber crime from characteristics of crime and offender. This study use qualitative methode that based on non numeric data e.g article and picture. The data filtern and interpreted by understanding the literature. Result of this study explain that there are there element that can be used in order to cyber crime analysis, there are system, provider, and law enforcer. This three element is key factor that can interfere, prevent cracker to commit crime and protect potential victim, and create safe and protected cyber environment. Recomendation of this study law enforcer must be strengthened by creating regualtion that can protect the user of cyber space. This is essential to minimize the number of data theft in the future.